The use of adapted boxing as a rehabilitation strategy in people with diverse health conditions: a systematic review - Miguel A. Sánchez-Lastra; Carlos Ayán; Mesut Sener; José M. Cancela (European Federation of Adapted Physical Activity, 2020)
Boxing exercise programs without direct contact with an opponent, is an adapted physical activity that integrate a series of tasks that may have positive effects on people with diverse health conditions. This study aimed to analyze the scientific evidence available on the effects of using adapted boxing as a rehabilitation strategy on people with diverse health conditions. A systematic review of the scientific literature was performed on studies which dealt with the effects of boxing as a rehabilitation strategy in people with diverse health conditions. Two modified scales were applied to assess the methodological quality of the findings. A total of 10 studies were included in the analysis, 4 of them were experimental and 6 observational. None of the studies reported injuries or other health complications derived from the exercise programs. The interventions led to improvements in cardiovascular fitness, upper body strength, body composition, coordination, gait independence and gait speed. The performance of adapted boxing is beneficial for people with diverse health conditions. Future randomized trials with larger samples would be needed to determine the most appropriate therapeutic dosing for each population.